The experience of organizing a problem solving lecture in the middle of the twentieth century - Holubnycha, L.; Moshynska , О. (Scientific notes of the pedagogical department, 2020)
The manuscript deals with organizing a problem solving lecture. It describes the experience of higher schools lecturers of the Eastern Ukrainian region in the middle of the twentieth century (the 50-60s). The research is significant because Ukraine seeks to raise the level of higher education and academic staff of the Universities is looking for appropriate forms and methods teaching in order to increase the efficiency of the organization of the student learning process. As leading teachers of the previous period have positive experience of organizing a problem solving lecture it may be useful to study it. The purpose of the article is generalizing features of the problem solving lectures on the basis of the analysis of positive experience of organizing them in higher schools of the Eastern Ukrainian region in the middle of the twentieth century (the 50-60s). The used research methods were general theoretical ones, namely analysis and synthesis of scientific sources under investigation as well as the historical retrospective method applied in historical investigation. The results revealed that lectures, which took more than 50% of time, played one of the most important roles in the organization of the educational process of Universities. Problem solving lectures were a priority for leading lecturers as they had a number of advantages. They are the following: 1) the problem solving lectures were the most economical way of learning; 2) they demonstrated to be efficient as for perception of educational material by students; 3) such lectures could be supposed as one of the most efficient ways of forming worldviews and principles; 4) they were a tool of intensification of students’ cognitive activity; 5) such lectures motivated students to active listening and participating in the lecture organization; 6) they were realized more accurately, remembered better and gave food for individual further thought. The prospects for further research may become practical, laboratory, seminar and other types of classes based on problem solving method, which were widely used together with the lectures during the studied period.